Numerical Assessment of Automotive Mufflers Using FEM, Neural Networks, and a Genetic Algorithm - Ying-Chun CHANG; Min-Chie CHIU; Meng-Ru WU (Archives of Acoustics, 2018)
In order to enhance the acoustical performance of a traditional straight-path automobile muffler, a multi-chamber muffler having reverse paths is presented. Here, the muffler is composed of two internally parallel/extended tubes and one internally extended outlet. In addition, to prevent noise transmission from the muffler’s casing, the muffler’s shell is also lined with sound absorbing material.